2017
DOI: 10.1021/acs.jnatprod.7b00648
|View full text |Cite
|
Sign up to set email alerts
|

Phenylpropenoids from Bupleurum fruticosum as Anti-Human Rhinovirus Species A Selective Capsid Binders

Abstract: The dichloromethane extract of the leaves of Bupleurum fruticosum was found to inhibit the replication of human rhinovirus (HRV) serotypes 14 and 39. Bioassay-guided fractionation led to the isolation of seven phenylpropenol derivatives (3-9), two polyacetylenes (1 and 2), and one monoterpene (10). Compounds 1 and 10 were identified as previously undescribed secondary metabolites after extensive 1D and 2D NMR experiments as well as high-resolution mass spectrometry. Compounds 2, 4, and 5 showed a selective inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 42 publications
(82 reference statements)
0
7
0
Order By: Relevance
“…Continuing our search for biologically active secondary metabolites from Sardinian higher plants 19,20 , we have found that the petroleum ether and ethyl acetate extracts of Magydaris pastinacea seeds exhibited potent inhibitory activity against hCA IX and XII. As a consequence, in order to identify the active compounds, a phytochemical investigation of the extracts was performed.…”
Section: Introductionmentioning
confidence: 99%
“…Continuing our search for biologically active secondary metabolites from Sardinian higher plants 19,20 , we have found that the petroleum ether and ethyl acetate extracts of Magydaris pastinacea seeds exhibited potent inhibitory activity against hCA IX and XII. As a consequence, in order to identify the active compounds, a phytochemical investigation of the extracts was performed.…”
Section: Introductionmentioning
confidence: 99%
“…During the continuous search of secondary plant metabolites with antiviral activity [24][25][26] , we found that the ethyl acetate (EtOAc) extract from the leaves of Teucrium flavum subsp. glaucum showed a significant inhibitory activity towards this enzyme function, with an IC 50 of 28.6 lg/mL (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…In the past, natural product chemists used to rely on polarimetry to draw conclusions about either enantiomeric purity or AC of isolated chiral secondary metabolites [ 27 ]. Even today, however, it is not unusual to find stereochemical assignments based on comparisons of chiroptical properties (optical rotation, sometimes measured in different conditions, and/or ECD) for structurally correlated compounds [ 28 , 29 , 30 ], or even based on biosynthetic considerations [ 31 , 32 ]. It is important to mention that herein we are not questioning the referenced assignments, but rather highlighting practices that may result in misassignments.…”
Section: Introductionmentioning
confidence: 99%